Simulating the Bird Eggs Illegal Trade and Improve the DNA Barcode Amplification to Combat Bird Trafficking Through Species Identification - Leandra Formentão; Daniela Núñez-Rodriguez; Andrea Rita Marrero (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics)
The illegal bird trade is changing from capturing live animals to smuggling eggs, making trafficking even more dangerous. Eggs can exhibit intraspecific variations or show very similar traits between different species, making the morphological species identification inaccurate. Thus, genetic species identification has become an essential tool in solving wildlife crimes. However, the conditions to which eggs are subjected during trafficking, from capture in the wild to seizure, make egg samples increasingly difficult even for DNA analysis, limiting the availability of biological material for species identification. We simulated different scenarios where eggs could be found and determined the best DNA barcode size to amplify in each situation. Chicken muscle tissue (Gallus gallus) and japanese quail eggs (Coturnix japonica) were submitted to adverse conditions resulting from trafficking: dried eggs, decomposing eggs, broken eggshells, and egg fluid deposited on various substrates. We assessed three salting-out DNA extraction protocols to find a cheaper and less toxic method. Different molecular markers from cytochrome oxidase I (COI) gene, fragments of 747, 405 and 164 bp, were tested. We successfully amplified the DNA mini-barcode (164 bp) in all simulations. However, the amplification of larger fragments was more challenging in complex samples such as decomposed eggs, egg fluid, and broken eggshells. These results demonstrate that DNA barcoding and mini-barcoding are powerful tools for identifying bird egg samples in various states of preservation, including decomposed samples. To apply this methodology as evidence in combating environmental crimes, we present a standardized flowchart for identifying bird species using molecular techniques.